A Legal Morality in Fullerian Jurisprudence (Raparin Journal of Humanities (RJH), 2021)
The American legal philosopher Lon L. Fuller profoundly advanced a sophisticated morality conception of law through his argument for thesis of Legal Morality (LM).  In particular, he adumbrated a novelist idea of “ internal morality of law” that would enable the transformation of the sophisticated morality conception of law into a conception idea of law and morality connection while simultaneously providing an explanation of the new and fresh thesis of legal morality. Contrary to the common (and mostly legal positivism) view, Fuller argues that it is not only the case that the (external) morality determines what the level of any connection between law and morality, rather it is also the idea of law in itself regenerates the idea of morality (internally). However, it is argued that in spite of the fact that Fuller suggested a sophisticated account of interconnection between law and morality, he fails to develop the complexities of the (morality) connection to the law in systemic way. What does he miss in his argument of the connection between law and morality? This study will advance the view that there are more than one way to make a connection between law and morality. Some of these connections can be named here: the morality of duty, the morality of legal subject, the morality of legal official, the morality of legal end, the morality of legal content and the internal and external morality of law. This study argues that each type of these connections between law and morality importantly has many effective outcomes in term of conception and implication of law, which Fuller did not tell us. In Fuller’s work, one can grasp the soundness of this connection in a variety levels. Yet, surprisingly to Fuller’s own works, this study will show that Fuller’s thesis of legal molarity must be expanded and justified on the different ground. In doing so, this study argues not only to make sense of Fuller’s legal morality, but it also redirects the systemic way to bring all pieces of Fuller’s claim of legal morality together and to seek the rationality beyond the legal.